Psychometric Properties of the Dutch Strengths and Difficulties Questionnaire (SDQ) in Adolescent Community and Clinical Populations. (October 2020) - Vugteveen, Jorien; de Bildt, Annelies; Serra, Marike; de Wolff, Marianne S.; Timmerman, Marieke E.
This study assessed the factor structures of the Strengths and Difficulties Questionnaire (SDQ) adolescent and parent versions and their measurement invariance across settings in clinical ( n = 4, 053) and community ( n = 962) samples of Dutch adolescents aged 12 to 17 years. Per SDQ version, confirmatory factor analyses were performed to assess its factor structure in clinical and community settings and to test for measurement invariance across these settings. The results suggest measurement invariance of the presumed five-factor structure for the parent version and a six-factor structure for the adolescent version. Furthermore, evaluation of the SDQ scale sum scores as used in practice, indicated that working with sum scores yields a fairly reasonable approximation of working with the favorable but less easily computed factor scores. These findings suggest that adolescent- and parent-reported SDQ scores can be interpreted using community-based norm scores, regardless of whether the adolescent has been referred for mental health problems.